2009
DOI: 10.1124/jpet.109.159806
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-Dependent Vasodilator Effects of Peroxisome Proliferator-Activated Receptor β Agonists via the Phosphatidyl-Inositol-3 Kinase-Akt Pathway

Abstract: Peroxisome proliferator-activated receptor ␤/␦ (PPAR-␤) is a ligand-activated transcription factor belonging to the nuclear hormone receptor superfamily that regulates the transcription of many target genes. More recently, acute, nongenomic effects of PPAR-␤ agonists have also been described. In the present study, we hypothesized that PPAR-␤ agonists might exert acute nongenomic effects on vascular tone. Here, we report that the structurally unrelated PPAR-␤ ligands [4-[3-(4-acetyl- sulfonyl]-2-thiophenecarbox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 41 publications
1
41
0
Order By: Relevance
“…22 Whereas, PPARδ agonists GW0742 and L-165041 at higher concentrations (>1 μmol/L) can directly induce vasodilatation, eNOS phosphorylation, and NO production. 23 In addition, our recent study demonstrated that another PPARδ agonist GW1516 protects endothelial function in diabetic db/db mice through an increase of eNOS activity and NO production. 7 The present data show that PPARδ mediates the effect of metformin in increasing eNOS phosphorylation in both mouse aortae and MAECs, as well as NO production, which are consistent with aforementioned observations that PPARδ improves NO bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…22 Whereas, PPARδ agonists GW0742 and L-165041 at higher concentrations (>1 μmol/L) can directly induce vasodilatation, eNOS phosphorylation, and NO production. 23 In addition, our recent study demonstrated that another PPARδ agonist GW1516 protects endothelial function in diabetic db/db mice through an increase of eNOS activity and NO production. 7 The present data show that PPARδ mediates the effect of metformin in increasing eNOS phosphorylation in both mouse aortae and MAECs, as well as NO production, which are consistent with aforementioned observations that PPARδ improves NO bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…It has been convincingly reported that PI3K and Akt are important upstream regulators of eNOS activation. 27,28,[39][40][41][42] eNOSderived NO has been known to have a pivotal role in the modulation of vascular tone and function. 6,7 Taken together, our results allow us to propose that, ROS/RNS excess in peripheral resistance vessels during I/R injury may blunt PI3K/Akt/eNOS pathway, thus triggering endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that eNOS is a novel substrate for Akt and Akt has a key role in promoting endothelial NO production and vasorelaxation. 27,28 Therefore, the phosphorylation of Akt was tested. The results of western blot analysis revealed that Akt phosphorylation was reduced after I/R, although total Akt showed equal protein levels in all samples (Po0.01 vs sham; Figure 7b).…”
Section: Effects Of I/r and Ipc Treatment On Pi3k And Akt Expression mentioning
confidence: 99%
“…9 PPAR␤ agonists also induce vasodilator effects in isolated aortas and mesenteric and pulmonary arteries. 10,11 Furthermore, a PPAR␤ agonist reduced the right heart hypertrophy and right ventricular systolic pressure in an experimental model of pulmonary arterial hypertension induced by chronic hypoxia. 11 We hypothesized that the PPAR␤ agonist GW0742 would reduce blood pressure, improving vascular inflammation and endothelial function in the spontaneously hypertensive rat (SHR).…”
mentioning
confidence: 99%